Structural diversity-guided optimization of carbazole derivatives as potential cytotoxic agents - Gao, Zilin; Chen, Yu; Nie, Yufei; Chen, Keming; Cao, Xiufang; Ke, Shaoyong (Frontiers in Chemistry, 2023)
Carbazole alkaloids, as an important class of natural products, have been widely reported to have extensive biological activities. Based on our previous three-component reaction to construct carbazole scaffolds, we introduced a methylene group to provide a rotatable bond, and designed series of carbazole derivatives with structural diversity including carbazole amide, carbazole hydrazide and carbazole hydrazone. All synthesized carbazole derivatives were evaluated for their in vitro cytotoxic activity against 7901 (gastric adenocarcinoma), A875 (human melanoma) and MARC145 (African green monkey kidney) cell lines. The preliminary results indicated that compound 14a exhibited high inhibitory activities on 7901 and A875 cancer cells with the lowest IC50 of 11.8 ± 1.26 and 9.77 ± 8.32 μM, respectively, which might be the new lead compound for discovery of novel carbazole-type anticancer agents.